Distribution and formation mechanism of residual stress in duplex stainless steel weld joint by neutron diffraction and electron backscatter diffraction. (5th November 2019) - Wan, Yu; Jiang, Wenchun; Song, Ming; Huang, Yalin; Li, Jian; Sun, Guangai; Shi, Yue; Zhai, Xiangnan; Zhao, Xu; Ren, Linchang
Abstract: The residual stress distribution of duplex stainless steel multi-pass weld joint and its formation mechanism still lacks systematic research. In this study, neutron diffraction and electron backscatter diffraction were used to systematically investigate the through-thickness residual stresses. The results show that both the macroscopic and macroscopic plus elastic mismatch residual stresses decrease along the through-thickness direction and the maximum area is located near the weld top surface. The elastic residual stresses in austenitic phase are larger in comparison to those in ferritic phase. In addition, tensile and compressive stress components are generally found in austenite and ferrite, respectively. Furthermore, it shows that higher level of high angle boundaries, Σ3 coincidence-site-lattice and local misorientation, which can generate larger thermal misfit plus plastic misfit residual stresses, are found in austenite. The formation mechanism of the residual stresses in both ferrite and austenite are also discussed. Graphical abstract: Unlabelled Image Highlights: Macroscopic plus elastic mismatch, macroscopic and elastic mismatch stresses were tested by neutron diffraction method. Both macroscopic and macroscopic plus elastic mismatch weld residual stresses decrease along through-thickness direction. The distributions of elastic mismatch residual stresses with respect to austenitic and ferritic phases are opposite. Grain boundary character distribution and local misorientation were used to assess thermal misfit plus plastic misfit stress.